Exploration and exploitation: the role of entrepreneurship and R&D in the process of innovation - Max Keilbach; Mark Sanders (Friedrich Schiller University Jena and Max Planck Institute of Economics, 2007)
We formulate a model that explicitly separates two functions in the innovation process: The introduction of new goods and the quality improvement of existing goods. While the latter is performed by the corporate R&D sector, the first is performed by entrepreneurs. We show that in a three sector economy, which also includes a producing sector, there exists a stable non trivial allocation of labor to production, innovation and entrepreneurship. We compute the steady state allocation of labor to production, R&D and Entrepreneurship. We show that the innovation rate decreases if one of the innovative sectors does not exist.
Keywords: O31; O41; 330; Innovation; Variety Expansion; Quality Ladders; Entrepreneurship; R&D Sector; Innovation; Produktqualität; Unternehmer; Industrielle Forschung; Mehr-Sektoren-Modell; Arbeit; Allokation; Dynamisches Gleichgewicht; Theorie